BEARING CAPACITY OF SPREAD FOUNDATIONS ON SAND OVERLYING CLAY - K. Yamamoto; D. Kim (Lowland Technology International, 2004)
Second, the kinematic approach of limit analysis has been used to calculate the upper bound of the true ultimate bearing capacity. The kinematic solutions are upper bounds and their accuracy depends primarily on the nature of the assumed failure mechanism. This approach makes it convenient to create design charts, and it is possible to trace the influence of parameters. Third, the commercial finite element program ABAQUS was applied to obtain the ultimate bearing capacity based on the elasto-plastic theory. Although FE anlysis has still not gained wide acceptance in foundation practice, FE analysishas the great advantages in which the equations of equilibrium and compatibility are solved together, compared with limit analysis. Finally, results obtained from the kinematic approach and the program ABAQUS were compared with those from the existing limit ewuilibrium equations proposed by Yamaguchi, Meyerhof and Okamura et al. for confirming the validity of their application to practice.